A Case Report of Obstructive Shock from an Esophageal Bolus Leading to Left Atrial Compression - Sharmin Kalam; Sergio Marquez; Emmelyn J. Samones; Tammy Phan; Vi Am Dinh (Clinical Practice and Cases in Emergency Medicine)
Introduction: Obstructive shock results from reduced cardiac output due to physical blockage of blood flow, such as cardiac tamponade. Cardiac tamponade compresses cardiac chambers, particularly the left atrium, causing decreased end-diastolic volume and cardiac output. Rapid fluid accumulation within the pericardial sac is the usual cause. Transesophageal echocardiography provides clearer visualization of these structures than transthoracic ultrasound. This case underlines the impact of esophageal pathology on cardiac output and highlights ultrasound’s dynamic diagnostic utility alongside computed tomography. Case Report: A 64-year-old female with a history of colon cancer and peritoneal metastases status post colostomy presented with altered mental status and urinary symptoms. Laboratory evaluation was notable for leukopenia, hypoglycemia, elevated ammonia, and an abnormal urinalysis that was positive for urinary tract infection. She was initially admitted to the internal medicine service for sepsis secondary to urine as the source of infection. During her hospital stay, she developed hypotension, tachypnea, tachycardia, and complained of chest pressure. Point-of-care echocardiogram revealed compression of the left atrium by distended gastric and esophageal contents. A nasogastric tube was placed and suctioned partially digested food and liquid with improvement of her condition. Follow-up ultrasound showed improvement of compression and cardiac function. Conclusion: In evaluation of acute shock, multiple etiologies must be considered. In this case, the cause of reduced cardiac output was direct compression of the left atrium from an adjacent structure. Even with direct visualization and imaging, immediate history and patient-centered approach are still useful to complete the clinical picture and treat the reversible cause of undifferentiated shock.